Optimum Generated Power with the Minimum Cost of a Radial Network using Firefly and Genetic Algorithms - Mohamed Els. S. Abdelwareth; Dedet Candra Riawan; Chow Chompoo‐inwai (My University, 2021)
This paper presented two artificial intelligence methods to find the optimum output power from Diesel generator (DG), Photovoltaic system (PV) and batteries to satisfy the load with the minimum cost considering the minimum losses. Our case study was a micro-gird 20 kV radial network consists of 21 busses located in Tomia island, south-east Sulawesi Island, Indonesia. Firefly algorithm (FA) and Genetic algorithm (GA) used in this study to do the optimization and chose the optimum operation. Forward-Backward sweep method used for the power flow calculations.
Keywords: Microgrid Control and Optimization; Optimal Power Flow Distribution; Energy Load and Power Forecasting